P344 Transmutation in high-risk sexual behavior of men in India: An assessment of magnitude and predictors. (14th July 2019) - Sharma, Santosh
Abstract : Background: Modern Indian society has witnessed rapid socio-cultural transformation where loosening of cultural values is observed at all levels. In the era of transition, traditional norms and values are at change where young male individuals are found to be associated with high-risk multi-partner sexual behaviour. This study intends to determine the changes in magnitude and predictors of such high-risk sexual behaviour among men in India. Methods: The sample of 74, 369 and 112, 122 men aged 15–54 from two rounds of the National Family Health Survey (NFHS) conducted during 2005–2006 (NFHS-3) and 2015–2016 (NFHS-4) has been used. The economic inequalities in the prevalence of high-risk sexual behaviour have been analysed using poor-rich ratio, and concentration index (CI) in addition to adjusted effects of major correlates through multiple logistic-regressions. Results: The burden of high-risk sexual behaviours over the last decade remains disproportionately higher among younger, unmarried, urban men and mainly from better economically households. Despite tremendous efforts of the governments in condom promotion as part of HIV/AIDS prevention programme, the improvements in condom use over the last decade, has not yet reached to the desired level. The disparities in high-risk sexual behaviour among men, coming from rich and poor households have been narrowed over the last decade. However, there are few states like Andhra Pradesh, Assam and Orissa where socio-economic inequalities in high-risk sexual behaviour have been increased. The findings also underline an apparent paradox in the relationship between knowledge of HIV/AIDS and indulgence into high-risk sexual behaviour and adopting safe sexual practices. Conclusion: It is recommended that all HIV prevention programmes in India should promote the concept of men as the responsible sexual partner. This concept may be promoted among young and unmarried men by reinforcing the shift from violence to respect and projecting the condom as sexual stimuli rather than a means of disease prevention. Disclosure: No significant relationships.